A Comparison between Hemodynamic Changes and Intraocular Pressure after Intubation with Endotracheal Tube, Laryngeal Mask Airway Classic™, and I-gel in Patients Candidate for Elective Eye Surgery - Akhondzade, Reza (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Hemodynamic changes following laryngoscopic tracheal intubation can trigger catecholamine release which consequently increases blood pressure and intraocular pressure (IOP) resulting in the disc rupture and ultimately blindness. Endotracheal intubation (endotracheal tube [ETT]) is a common technique for stress response management. The present study aims to comparatively investigate the hemodynamic changes and IOP after three intubation approaches of ETT, laryngeal mask airway (LMA) Classic™, and I-gel in patients undergoing elective cataract surgery. Materials and Methods: This clinical trial was conducted on 75 patients with ASA classes I and II (age range: 50–65 years old) who were the candidate for elective cataract surgery admitted in Ahvaz Imam Hospital, Iran, during 2013–2014. The hemodynamic changes and IOP values were measured in the patients before and after intubation with ETT, LMA Classic™, and I-gel. The pulse rate, systolic and diastolic blood pressures, and IOP were measured at four intervals at 1 minute before and at 1, 2, and 5 min after the insertion of the airway devices. The IOP was measured with Tonopen. Results: Immediately, before inserting ETT, LMA, and I-gel, the heart rate, systolic and diastolic blood pressures significantly increased in all groups. The results showed that the hemodynamic changes and IOP following I-gel were more stable than the LMA Classic™ and ETT devices. In addition, the LMA Classic™ intubation showed more stable hemodynamic response than the ETT. Conclusions: The findings showed that I-gel intubation results in more stable hemodynamic responses in elective cataract surgery.